Rol del personal de salud en la atención a las mujeres maltratadas (2001)
ABSTRACT: Domestic violence against women, a worldwide epidemiological problem that results in serious mental and physical damage of women, is an issue that is not recognized as such by healthcare institutions. As such, thousands of Colombian women are not diagnosed and cared for as a whole. This article reflects upon this situation and describes the components of the process of integral care for the abused woman that pertains to healthcare institutions.